Kekuatan Hukum Putusan Dewan Kehormatan Penyelenggara Pemilu terhadap Penetapan Calon Presiden dan Wakil Presiden - Dananjaya, Adhitya Arum; Hadi, Syofyan (Journal Evidence Of Law, 2025)
This research discusses the legal strength of the decision of the Election Organizer Honorary Council (DKPP) regarding the determination of presidential and vice presidential candidates by the General Election Commission (KPU). DKPP is an institution tasked with enforcing the code of ethics for election organizers by issuing final and binding decisions. However, this "final and binding" nature is often questioned in the context of whether DKPP decisions are equivalent to decisions of formal judicial institutions. This research highlights the legal strength of DKPP decisions in the context of determining presidential and vice presidential candidates, especially in cases of violations of the code of ethics by the KPU. Through normative research methods that examine statutory regulations and juridical analysis, this research finds that although DKPP decisions are binding for election management institutions such as the KPU and Bawaslu, these decisions do not have permanent legal force like formal judicial decisions and can become the object of a lawsuit in court. State Administration (PTUN). The research results show that although the DKPP decision is final and binding on the relevant agencies, it is limited in nature as part of internal supervision and can become the object of a lawsuit in the state administrative court. This confirms that the DKPP does not have the same legal power as formal justice, even though its decisions must be implemented by the parties involved in holding elections.